GLOBALIZATION OF CHINESE HIGHER EDUCATION AS A FACTOR OF GEOPOLITICAL INFLUENCE - V. V. Kuznetsova; O. A. Mashkina (Сравнительная политика)
The competitiveness of the country in the modern world mainly depends on the ability of the national education system to provide training for the professional elite, to involve the broad strata of society in the process of lifelong learning and to create conditions to meet the various cultural and socioeconomic needs of the population. The Chinese dominant national idea − the revival of greater China − in the most important documents is supplemented recently by new content: “the creation a powerful country with a strong education.” Education in China’s strategy is considered as a main factor of social stability and internal ethnic integration, and at the same time as an engine of innovative development. China provides the world with an example of how to increase the potential of human capital in a country where illiteracy and poverty reigned 30 years ago. The Chinese higher education system not only demonstrates its ability to compete with the world’s leading universities, but also promotes its technologies, standards and values in the global educational space, fi rst of all, strengthening its infl uence on the countries included in the “One Road ‒ One Road” project.